Combination of modified albumin-bilirubin grade and platelet count to predict high-risk varices in patients with hepatocellular carcinoma - Prooksa Ananchuensook; Kingkomon Piyawannasuth; Sirinporn Suksawatamnuay; Panarat Thaimai; Nipaporn Siripon; Supachaya Sriphoosanaphan; Kessarin Thanapirom; Piyawat Komolmit (PLoS ONE, 2025)
Background Variceal bleeding is associated with poor prognosis in patients with hepatocellular carcinoma. Therefore, it is essential to identify indicators of high-risk varices (HRV) and provide prompt intervention. Aim To validate and modify albumin-bilirubin and platelet scores to predict high-risk varices in patients with hepatocellular carcinoma. Methods We enrolled patients with hepatocellular carcinoma and esophagogastroduodenoscopy reports at King Chulalongkorn Memorial Hospital, Bangkok, Thailand, between 2015 and 2022. The nearest demographic and clinical characteristics and laboratory values were reviewed retrospectively within 6 months before the esophagogastroduodenoscopy. Albumin-bilirubin and platelet counts were calculated from the albumin-bilirubin grade plus score from platelet count. We evaluated the new modified albumin-bilirubin and platelet (mALBI-PLT)‘s in predicting HRV by dividing participants into a training cohort (first half) and a validation cohort (second half). Results Of 564 patients with hepatocellular carcinoma, 277 were included. Most patients (232 [83.8%]) had Child-Turcotte-Pugh A cirrhosis, whereas 131 (47.3%), 85 (30.7%), and 60 (22.0%) had Barcelona Clinic Liver Cancer stages A, B, and C, respectively. Thirty-eight (15.6%) participants had HRV on esophagogastroduodenoscopy. On multivariate analysis, modified albumin-bilirubin grades 2b and 3 and platelet count ≤150,000/µL were significantly associated with HRV. With a cut-off value of 2, the mALBI-PLT showed comparable performance in both cohorts, yielding sensitivities of 93.8% and 95.5%, and negative predictive values (NPV) of 98.1% and 98.0%, respectively. In the entire cohort, the albumin-bilirubin and platelet scores, and mALBI-PLT score >2, demonstrated excellent sensitivities (97.4% and 94.7%), respectively, (with NPV of 98.7% and 98.0%), in predicting HRV. Conclusion Modified albumin-bilirubin grade and platelet at cut-off 150,000/µL exhibited significant association with high-risk varices in patients with hepatocellular carcinoma. Moreover, hepatocellular carcinoma patients with modified albumin-bilirubin grade 1 or 2a, together with platelets > 150,000/µL, may be able to avoid oesophagogastroduodenoscopy.